Biofiltration and Physicochemical Filtration for Water Treatment - Osorio, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Biofiltration is a technology of great interest since the costs of installation and, above all, exploitation costs are much lower than those associated with other technologies based on physical-chemical processes. Nowadays, the use of biofiltration is increasing every day. On the other hand, the physicochemical filtration process is a successful technology in numerous applications in the field of water treatment. This issue of the journal is focused on the treatment of different types of effluents through filtration: Drinking water and wastewater. Different technologies are analysed: Filtration through biochar from agricultural by-products; biological active carbon (BAC); electroadsorption using a commercial granular activated carbon as the adsorbent; filtration through sand, anthracite and expanded clay; granular activated carbon (GAC) as part of a tertiary treatment for wastewater reuse.